Comparative Reliability Analysis between Horizontal-Vertical-Diagonal Code and Code with Crosstalk Avoidance and Error Correction for NoC Interconnects (Journal of Engineering, 2023)
Ensuring reliable data transmission in Network on Chip (NoC) is one of the most challenging tasks, especially in noisy environments. As crosstalk, interference, and radiation were increased with manufacturers' increasing tendency to reduce the area, increase the frequencies, and reduce the voltages.  So many Error Control Codes (ECC) were proposed with different error detection and correction capacities and various degrees of complexity. Code with Crosstalk Avoidance and Error Correction (CCAEC) for network-on-chip interconnects uses simple parity check bits as the main technique to get high error correction capacity. Per this work, this coding scheme corrects up to 12 random errors, representing a high correction capacity compared with many other code schemes. This candidate has high correction capability but with a high codeword size. In this work, the CCAEC code is compared to another well-known code scheme called Horizontal-Vertical-Diagonal (HVD) error detecting and correcting code through reliability analysis by deriving a new accurate mathematical model for the probability of residual error Pres for both code schemes and confirming it by simulation results for both schemes. The results showed that the HVD code could correct all single, double, and triple errors and failed to correct only 3.3 % of states of quadric errors. In comparison, the CCAEC code can correct a single error and fails in 1.5%, 7.2%, and 16.4% cases of double, triple, and quadric errors, respectively. As a result, the HVD has better reliability than CCAEC and has lower overhead; making it a promising coding scheme to handle the reliability issues for NoC.